Comprehensive geriatric assessment for oral care in older adults: a focus group study - Nattariya Wongiam; Kearkiat Praditpornsilpa; Anjalee Vacharaksa (BMC Geriatrics)
Abstract Background An increase in the aging population underscores the need for oral healthcare practice guidelines. Comprehensive geriatric assessment (CGA) includes multidimensional evaluation and integrates oral health into overall healthcare. However, a framework for CGA in dental setting has not been clearly structured. This study aimed to identify the components of CGA essential for proper oral care in older adults based on the perspective of multidisciplinary experts. Methods A scoping review was conducted to provide insights into CGAs that are mentioned in treatment plan models for oral healthcare (Protocol registration number 10.17605/OSF.IO/EZRDV). The findings were used as basic information for focus group discussion among the multiple healthcare professions. The first focus group included 6 medical experts of 6 disciplines, and the second focus group included 6 dental experts. Focus group discussion aimed to provide a rationale for selecting CGA components and assessment tools that were essential. Thematic analysis was used to synthesize expert perspectives and build an agreement on the application of CGAs in dental practice. Results The scoping review revealed four dental treatment planning models, including the OSCAR model, rational treatment model, the Seattle Care Pathway, and the risk of oral health deterioration (ROHD). These models suggested the key CGA components, including systemic conditions for any risks of comorbidities, oral health conditions, socioeconomic status, dependency, cognitive and mental health, communication, and life expectancy. Data from both focus groups consistently agreed that dentists should evaluate complex oral problems of older adults in multiple dimensions. In addition, they also emphasized the importance of swallowing problems, nutrition, and fall risk. Nonetheless, the selection of assessment tools such as The Barthel Index for Activities of Daily Living, water swallow screening test, Mini Nutritional Assessment, Mini-Cog, Patient Health Questionnaire, and three key questions for fall risk assessment should depend on the purposes and team expertise. The development of dental treatment plans must be individualized based on evaluation results of CGA. The rationale for different treatment levels, including comprehensive, limited, urgency care and no treatment, was discussed. The focus groups emphasized that dependency level, social support and systemic factors were important for selecting a level of care. Conclusions CGA provides rationale for oral health problem analysis, treatment planning, and oral healthcare. The expert opinions underscore the importance of comprehensive and individualized care plans suggested in the oral treatment plan model. The multiple dimensions of CGAs include systemic and oral health, socioeconomic factors, dependency, cognitive and mental health, swallowing problem, nutrition, and fall risk. The selection of assessment tools should be optimized based on the purposes and team expertise. The multidisciplinary team has a crucial contribution in comprehensive evaluation of patient problems when formulating treatment plans for special-needed patients.